Improving Student Learning Outcomes in Science and Technology Learning Through Image Media in Class V of SD Negeri 01 Ulak Karang Selatan - Rafda, Novia; Oktira , Yona Syaida; Efendi, Nofriza; Ayunis, Ayunis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research is classroom action research. The problem encountered by researchers is that teachers teach using the lecture method and do not use other methods, the teacher's teaching strategy is too monologue and does not use learning media. Efforts to improve the ability to learn science and technology have a learning approach that links several science lessons taught by teachers to students using image media in cycle 1, science learning taught by teachers to students using image media in cycle 2 to increase student learning outcomes. This research aims to determine student learning outcomes after using image media. This research will also be useful for teachers and schools to improve student learning outcomes. The type of research in this research is classroom action. Data collection techniques are: observation, tests, and documentation. The results of the research show initial conditions, namely the pre-cycle of student learning outcomes in science and science learning with an average score of 67 with a completion percentage of 57% in the very poor category. In the first cycle, student learning outcomes in science and science learning obtained an average score of 77 with a completion percentage of 71% in the poor category, and in cycle II the average student score was 80 with a percentage of 92% in the good category. Thus it can be concluded that Image Media can improve student learning outcomes as seen from the LKPD of class V students at SD Negeri 01 Ulak Karang Selatan in science and science learning.